ROSANA RUBIO Y FERNANDO NIETO (eds.) - Arquitectura de la soledad - Martín, Guiomar (ZARCH, 2025)
ROSANA RUBIO, FERNANDO NIETO (eds.) Arquitectura de la soledad Ed. Asimétricas, Madrid, 2024, 248 pp. Tapa blanda. Idioma: español. 24 € ISBN 978-84-10065-09-3